Succession involving wealth from unlawful sources under Islamic law of inheritance - Hj Ibrahim, Badruddin (2018)
This study examines the issue of succession involving wealth from unlawful sources under Islamic law of inheritance. The question is whether legal heirs entitle to inherit a deceased in case if the wealth of the deceased comes from unlawful sources like usurpation, breach of trust, interest (riba), gambling, trading of prohibited items such as wine, drug, swine etc. In other words, whether Islam recognizes wealth from unlawful sources as the estate and whether the ownership of the wealth from unlawful sources is established on legal heir by means of inheritance? The discussion focuses on the meaning of succession and its rule, meaning of wealth from unlawful sources, and the position of Islamic law regarding the succession of the wealth from unlawful sources. The discussion also investigates Islamic legal maxim “changing of a cause of ownership is the ground of the changing of the position of thing (wealth)”, whether it is applicable to the issue of the inheritance of unlawful wealth? The study examines the issue from the perspective of the Qur’an and the Sunnah as primary sources of Islamic law. Examination extends to the view of the Muslim jurists of four well known schools of law as well as contemporary Muslim scholars.